HGG-18. Long-term efficacy and safety of larotrectinib in paediatric patients with tropomyosin receptor kinase (TRK) fusion-positive primary central nervous system (CNS) tumours. (3rd June 2022) - Nysom, Karsten; Doz, François; Geoerger, Birgit; Øra, Ingrid; Perreault, Sebastien; Norenberg, Ricarda; Fellous, Marc; De La Cuesta, Esther; Laetsch, Theodore W; van Tilburg, Cornelis M
Abstract: INTRODUCTION : Neurotrophic tyrosine receptor kinase ( NTRK ) gene fusions are oncogenic drivers in various tumours. Larotrectinib, a highly selective TRK inhibitor, demonstrated an objective response rate (ORR) of 75% across 206 evaluable patients with various non-primary CNS cancers (Hong et al, ASCO 2021). We report long-term data on larotrectinib-treated paediatric patients with TRK fusion-positive primary CNS tumours. METHODS : Patients aged <18 years with TRK fusion-positive primary CNS tumours enrolled in two clinical trials (NCT02637687, NCT02576431) were included. Larotrectinib was administered at 100 mg/m 2 (maximum: 100 mg) twice-daily. Response was investigator-assessed per RECIST v1.1 and RANO. RESULTS : As of July 2021, 28 patients with TRK fusion-positive primary CNS tumours were enrolled, including 14 high-grade and eight low-grade gliomas. Median age at enrolment was 7.0 years (range 1.0–17.0). Twenty-three patients (82%) received prior systemic therapy and 12 (43%) received prior radiotherapy. The ORR was 39% (95% confidence interval [CI] 22–59): three complete responses, eight partial responses, 15 stable disease and two progressive disease. The 24-week disease control rate was 82% (95% CI 63–94). Median duration of response (DoR) was not reached; median follow-up was 25.6 months. Median progression-free survival was 21.9 months (95% CI 9.2–not estimable). Median overall survival (OS) was not reached; median follow-up was 27.6 months. DoR and OS 24-month rates were 53% and 71%, respectively. Treatment duration ranged from 1.0 to 39.0+ months. Treatment-related adverse events (TRAEs) were mostly Grade 1–2. Grade 3–4 events occurred in three patients (increased gamma-glutamyltransferase, hyperglycaemia, hypernatraemia, hyponatraemia and neutropaenia). No patients discontinued treatment due to TRAEs. Fourteen patients progressed on treatment; four continued treatment post-progression for ≥4 weeks. CONCLUSION : Larotrectinib demonstrated high disease control rate, durable responses and a manageable safety profile. These results support testing for NTRK gene fusions in paediatric patients with primary CNS tumours.